Pengaruh Media Big Book Wordless Picture Book Bertema Kindness Terhadap Kemampuan Berbicara Anak - Nilnaa Qurrota A'yun Ar; Sri Widayati; Mallevi Agustin Ningrum; Kartika Rinakit Adhe (Universitas Muhammadiyah Gresik, 2023)
The ability to speak is a basic ability that must be mastered by every human being in order to be able to interact and take a role in social life. Speaking is a form of language skills so that in order for children to more easily convey their ideas and thoughts, educators should stimulate children's speaking abilities to the fullest. This pre-experimental quantitative research type of one group pretestposttest design aims to compare two variables, namely the influence of the media big book wordless picture book themed kindness on the speaking ability of children aged 3-4 years at Nada Ashobah Wiyung KB with a sample of 11 children. The data collection technique used was observation with indicators of phonology, morphology, syntax, semantics, and pragmatics. The analysis technique used in this study is non-parametric statistics using the Wilcoxon Match Pairs Test. The results showed that the Wilcoxon test obtained an Asymp (2-tailed) value of 0.003 <0.05 indicating the null hypothesis (H0) was rejected meaning there was an influence. This means that the big book wordless picture book media with the theme of kindness influences the speaking ability of children aged 3-4 years at the Nada Ashobah Wiyung KB Surabaya. Keywords: Wordless Picture Book, Speaking Ability